Relation Entre Éclairs Nuage-Sol et Précipitations Pendant la mousson 2006 au Bénin - HOUNGNINOU, BODOUN ETIENNE; ADECHINAN, A. Joseph; MOUMOUNI, Sounmaila; GUEDJE, KOSSI FRANÇOIS; ALLE, C. S. ULRICH; KOUGBEAGBEDE, Hilaire; HOUNGNINOU, T. ERIK (My University, 2013)
The study that is submitted to you highlights the relationship between Cloud-to- Ground lightning (CG) and precipitations during the monsoon of 2006 in Benin at the Oueme Upper Valley Hydrometeorological Observatory. The lightning data used are obtained from the LINET network and the ones of the precipitations are from the 49 rain gauges. The results show clearly that the spatial density of the lightning (fl per flash) greatly vary with an average of 26 fl/km2. The number of the cloud-to-ground lightning globally increases with latitude whereas it decreases with longitude. Temporal and spatial scales used to determine the value of rain yield (i.e the ratio of total precipitation to CG flash counted over a common area) are respectively 1 month and 100 km2. These values vary between 1.5 107 and 49 107 kg/fl with an average 7.9 107 kg/fl. The average correlation coefficient between the precipitations and the cloud-to-ground lightning during the monsoon of 2006 is 0.55. The contribution of the convective precipitations to the total rain fall is estimed to 50% in the North-West, 40 % in the South-Est, 22 % in the North-Est and 21 % in the South-West of the Oueme Upper Valley Hydrometeorological Observatory.
Keywords: éclair nuage-sol; précipitation; ratio pluie-éclair; mousson